2011
DOI: 10.1163/cl-2011-033
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to climate change adaptation in the Netherlands

Abstract: Review of recent literature on adaptation to climate change and general literature on policy processes shows that there are a large number of barriers that hamper the development and implementation of climate change adaptation strategies. To reduce and manage the number of barriers and combine both streams of literature, we propose seven clusters of barriers to adaptation. Little is known, however, about the relative importance of these barriers to climate change adaptation policies and practices. An online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 0 publications
4
110
1
1
Order By: Relevance
“…Our and others' results suggest that institutional setting is crucial in water management, especially for the coordination of roles and compromises among different stakeholders. Biesbroek et al (2011) also found that among the most highly ranked barriers to climate change adaptation in the Netherlands -besides short term thinking of the politicians versus long term dynamics of climate change -are conflicting interests (corresponding to our heterogeneity of interests), lack of financial resources, and unclear division of tasks and responsibilities. The results of our study suggested that availability of resources (in particular financial resources) is potentially one of the most constraining CIPs for the implementation of adaptation measures in agriculture.…”
Section: Institutional Feasibilitymentioning
confidence: 90%
See 4 more Smart Citations
“…Our and others' results suggest that institutional setting is crucial in water management, especially for the coordination of roles and compromises among different stakeholders. Biesbroek et al (2011) also found that among the most highly ranked barriers to climate change adaptation in the Netherlands -besides short term thinking of the politicians versus long term dynamics of climate change -are conflicting interests (corresponding to our heterogeneity of interests), lack of financial resources, and unclear division of tasks and responsibilities. The results of our study suggested that availability of resources (in particular financial resources) is potentially one of the most constraining CIPs for the implementation of adaptation measures in agriculture.…”
Section: Institutional Feasibilitymentioning
confidence: 90%
“…Recent literature on adaptation reveals different terms used to describe factors that may hinder implementation of adaptation from an institutional perspective (see review paper of Biesbroek et al (2013) Moser and Ekstrom (2010) and Biesbroek et al (2011) speak about barriers to climate change adaptation. Gupta et al (2010) focus on assessment of adaptive capacity of institutions and propose an assessment framework called the adaptation wheel.…”
Section: Framework To Assess Institutional Factors Influencing Adaptmentioning
confidence: 99%
See 3 more Smart Citations